2020
DOI: 10.36227/techrxiv.12195870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Far UV-C lights and fiber optics induced and selective far UV-C treatment against COVID-19 for fatality-survival tradeoff

Abstract: <p>This work focuses on the usability of Ultraviolet (UV) on humans as an economical way of contesting against COVID-19. Specifically, far-UVC is presented as a promising candidate against COVID-19 since it can inactivate pathogens including viruses and bacteria without harming mammalian skin or eyes. Furthermore, the work also points out the applicability of far-UVC lights for public spaces and treatment of selective region in COVID-19 patients by using fiberoptic as the medium for high-risk cases where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…To support the use on surfaces was considered on the dose of germicides next to hydrogen peroxide and based on xenon (PX-UVC) can reduce nosocomial pathogens on the surfaces of hospital places. [38], [44], [19] 2 75%><90% 4 [48], [24], [33], [47] 3 <95% 3 [39], [36], [40] IV. DISCUSIÓN Many studies have shown that UV light can be used in different ways.…”
Section: Fig 6 Percentages Of Evidence In Resultsmentioning
confidence: 99%
“…To support the use on surfaces was considered on the dose of germicides next to hydrogen peroxide and based on xenon (PX-UVC) can reduce nosocomial pathogens on the surfaces of hospital places. [38], [44], [19] 2 75%><90% 4 [48], [24], [33], [47] 3 <95% 3 [39], [36], [40] IV. DISCUSIÓN Many studies have shown that UV light can be used in different ways.…”
Section: Fig 6 Percentages Of Evidence In Resultsmentioning
confidence: 99%
“…In vitro investigations have reported that extremely small doses of 1.2 to 1.7 mJ cm −2 of far UV-C 222-nm light inactivated aerosolized H1N1 influenza virus and coronaviruses [ 6 , 12 ]. It has been reported that UV-C 207–222-nm is a promising candidate against COVID-19 propagation, as this radiation would inactivate SARS-CoV-2 and other hazardous microorganisms that contaminate surfaces in public spaces without harming mammalian skin or eyes [ 13 ]. Ozone produced from ambient air can be considered a side effect of far UV-C lamp operation, although it is well known for its killing action against bacteria, fungi, and viruses [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%